Well, darling, 3x plus 6y plus 6x simplifies to 9x + 6y. That's all there is to it, sugar. Math doesn't have to be complicated, just like your love life!
No, probably not.
This simplifies to 6+13y If you meant 9+7y-(3+6y) then it becomes 6+y It is not clear from the problem which you meant.
y = ½ (6y = 3)
6x + 3y + 6y - 2x = (6x - 2x) + (3y + 6y) = 4x + 9y
-6y + 14 + 4y = 32-2y = 32 - 14-2y = 18y = - 9
6y + 8 = 32 6y + 8 - 8 = 32 - 8 6y = 24 6y/6 = 24/6 y = 4
6y = 12x+32 Divide all terms by 6: y = 2x+5 and 1/3 which is now in slope intercept form
-6y+3 = -7y+8 -6y+7y = 8-3 y = 5
6y-1+8=32 y=4 1/6 Here's the steps- 6y-1+8=32 6y+7=32 6y=25 y=4 1/6
2x plus 6y equals 32 32 divided by 6= 5 R2 5+2= 7x6= 42-5=37-2=35 so X=5
Well, darling, 3x plus 6y plus 6x simplifies to 9x + 6y. That's all there is to it, sugar. Math doesn't have to be complicated, just like your love life!
(4y2 + 3)(4y2 - 6y + 3)(4y2 + 6y + 3)
It can be simplified to: 3+y
6y-1+8=32 first add -1+8 then your answer move it to the other side of the equation 6y=25 then divide by 6 to live y alone y=25/6
6y + 2 = y + 17 => 5y = 15 => y = 3
No, probably not.